Current Advances in the Diagnosis and Treatment of Nonerosive Reflux Disease - Chen, Chien-Lin (Hindawi Publishing Corporation, 2013)
Nonerosive reflux disease (NERD) is a distinct pattern of gastroesophageal reflux disease (GERD). It is defined as a subcategory of GERD characterized by troublesome reflux-related symptoms in the absence of esophageal mucosal erosions/breaks at conventional endoscopy. In clinical practice, patients with reflux symptoms and negative endoscopic findings are markedly heterogeneous. The potential explanations for the symptom generation in NERD include microscopic inflammation, visceral hypersensitivity (stress and sleep), and sustained esophageal contractions. The use of 24-hour esophageal impedance and pH monitoring gives further insight into reflux characteristics and symptom association relevant to NERD. The treatment choice of NERD still relies on acid-suppression therapy. Initially, patients can be treated by a proton pump inhibitor (PPI; standard dose, once daily) for 2–4 weeks. If initial treatment fails to elicit adequate symptom control, increasing the PPI dose (standard dose PPI twice daily) is recommended. In patients with poor response to appropriate PPI treatment, 24-hour esophageal impedance and pH monitoring is indicated to differentiate acid-reflux-related NERD, weakly acid-reflux-related NERD (hypersensitive esophagus), nonacid-reflux-related NERD, and functional heartburn. The response is less effective in NERD as compared with erosive esophagitis.